Manager Regime of Social and Solidarity Economy Entities in Latin America: Manager Regime of Social and Solidarity Economy Entities in Latin America - García Müller, Alberto (Cooperativismo & Desarrollo, 2013)
This paper relates the legal regime from both a legislative and a doctrinal point of view, in the Latin American context, applicable to the figure of the manager of the entities of social and solidary economy (eess for its initials in Spanish) as its key player, largely responsible for both the successes and failures that these entities achieve.